Empowerment Based on Social Solidarity in the Management System of Sharia Homestay by the Muslim Community in Dieng Kulon Village - Sucipto, Sucipto (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2025)
The tourism sector is one of the shortcuts to stimulate the economic development of a community. However, the significant growth potential is also accompanied by various risks, including negative impacts on social, cultural, and even economic aspects. This prompted the community in Dieng Kulon village to adopt a different approach in response to the rapid tourism development in the Dieng Plateau. Using a qualitative research method with a phenomenological approach, this article aims to explore how social solidarity-based empowerment of the Muslim community is implemented in the management system of Sharia homestay in Dieng Kulon village. The findings of this study indicate that social solidarity-based empowerment in the management system of Sharia homestay can be successful because the community possesses social capital in the form of land assets, as well as social solidarity in the form of trust, mutual assistance, and mutually beneficial cooperation. Furthermore, the social solidarity is derived from two factors: genetic, as most of the Dieng Kulon community is still bound by kinship ties (family); and even if not through kinship, there is a sense of shared identity as natives of Dieng Kulon. These factors bind the community of Sharia homestay entrepreneurs in Dieng Kulon to remain committed to achieving shared welfare while upholding Islamic values, norms, and teachings.